Peculiarities of Tax Residency of Individuals in Modern Conditions - BONDARENKO, Iryna M.; BURDIN, Mykhailo Yu.; KAGANOVSKA, Tetyana Ye.; LATKOVSKA, Tamara A.; PONOMARENKO, Yuriy A.; NADOBKO, Serhii V. (Journal of Advanced Research in Law and Economics, 2019)
The article is devoted to the study of tax residency of an individual in the context of globalization and modern conditions of international cooperation.